Engineering of Bismuth Oxide Nanoparticles to Induce Differential Biochemical Activity in Malignant and Nonmalignant Cells. (9th April 2014) - Stewart, Callum; Konstantinov, Konstantin; McDonald, Marjorie; Bogusz, Kathrin; Cardillo, Dean; Oktaria, Sianne; Shi, Dongqi; Lerch, Michael; Devers, Thierry; Corde, Stéphanie; Rosenfeld, Anatoly; Tehei, Moeava
<x xml:space="preserve">Abstract</x> The relationship between cytotoxicity and the levels of oxidative stress is reported with respect to annealing atmosphere in malignant 9L gliosarcoma tumor and nonmalignant Madin‐Darby canine kidney cell lines. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>